2018
DOI: 10.1158/2159-8290.cd-17-1371
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Derived Lipids Mediate Melanoma Progression via FATP Proteins

Abstract: Advanced, metastatic melanomas frequently grow in subcutaneous tissues and portend a poor prognosis. Though subcutaneous tissues are largely composed of adipocytes, the mechanisms by which adipocytes influence melanoma are poorly understood. Using and models, we find that adipocytes increase proliferation and invasion of adjacent melanoma cells. Additionally, adipocytes directly transfer lipids to melanoma cells, which alters tumor cell metabolism. Adipocyte-derived lipids are transferred to melanoma cells thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
282
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 284 publications
(296 citation statements)
references
References 68 publications
10
282
1
3
Order By: Relevance
“…Cellular components in the tumor microenvironment are major regulators of tumor metabolism, driving cancer cells to favor certain metabolic pathways (Gouirand et al, 2018). Indeed, tumor secretions trigger lipolysis in neighboring adipocytes (Dirat et al, 2011), and the released FA fuel fatty acid oxidation (FAO) in tumors, which increases tumor aggressiveness (Nieman et al, 2011;Balaban et al, 2017;Wang et al, 2017;Zhang et al, 2018). Indeed, tumor secretions trigger lipolysis in neighboring adipocytes (Dirat et al, 2011), and the released FA fuel fatty acid oxidation (FAO) in tumors, which increases tumor aggressiveness (Nieman et al, 2011;Balaban et al, 2017;Wang et al, 2017;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular components in the tumor microenvironment are major regulators of tumor metabolism, driving cancer cells to favor certain metabolic pathways (Gouirand et al, 2018). Indeed, tumor secretions trigger lipolysis in neighboring adipocytes (Dirat et al, 2011), and the released FA fuel fatty acid oxidation (FAO) in tumors, which increases tumor aggressiveness (Nieman et al, 2011;Balaban et al, 2017;Wang et al, 2017;Zhang et al, 2018). Indeed, tumor secretions trigger lipolysis in neighboring adipocytes (Dirat et al, 2011), and the released FA fuel fatty acid oxidation (FAO) in tumors, which increases tumor aggressiveness (Nieman et al, 2011;Balaban et al, 2017;Wang et al, 2017;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes, the main component of AT, reside in many cancer microenvironments and contribute to tumor progression through soluble factors, such as leptin or interleukin 6, and extracellular matrix remodeling (Andarawewa et al, 2005;Dirat et al, 2011;Duong et al, 2017). Recent findings highlight a metabolic cooperation between adipocytes and tumor cells, which is proving to be a key process in their tumor-promoting effects (Nieman et al, 2011;Balaban et al, 2017;Wang et al, 2017;Zhang et al, 2018). Cellular components in the tumor microenvironment are major regulators of tumor metabolism, driving cancer cells to favor certain metabolic pathways (Gouirand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blask and colleagues found that increased FATPs enhance FA uptake in rat hepatomas . Zhang et al showed that melanoma cells express FATPs, and that these proteins mediate transport of FAs from subcutaneous adipocytes to the tumor cells, which utilize FAs to fuel their growth and proliferation . Interestingly, blocking FATP reduced melanoma growth and lipid content both in in vitro and in vivo studies .…”
Section: Multiple Myeloma and Fatty Acid Metabolismmentioning
confidence: 99%
“…Zhang et al showed that melanoma cells express FATPs, and that these proteins mediate transport of FAs from subcutaneous adipocytes to the tumor cells, which utilize FAs to fuel their growth and proliferation . Interestingly, blocking FATP reduced melanoma growth and lipid content both in in vitro and in vivo studies . However, as it is not clear yet how FATPs mediate FA uptake, and which FATPs have FA uptake and acyl‐CoA synthetase activity, more research into the roles of FATPs in cancer is needed.…”
Section: Multiple Myeloma and Fatty Acid Metabolismmentioning
confidence: 99%